Safety and efficacy of catheter ablation in atrial fibrillation patients with heart failure with preserved ejection fraction - Songbing Long; Yuanjun Sun; ShiYu Dai; Xianjie Xiao; Zhongzhen Wang; Wei Sun; Lianjun Gao; Yunlong Xia; Xiaomeng Yin (BMC Cardiovascular Disorders)
Abstract Purpose Catheter ablation (CA) for atrial fibrillation (AF) in heart failure patients with preserved ejection fraction (HFPEF) has shown promising results in reducing mortality and improving heart function. However, previous studies have been limited by a lack of control groups and significant heterogeneity in their methodologies. Hypothesis CA for AF in HFPEF patients may not increase the complications and had similarly the rate of freedom from AF vs. patients without HFPEF, and it may reduce hospitalizations and mortality and improve heart function VS medical treatment. Methods Three groups of AF patients were included in the study: 187 patients with HFPEF for their first CA (AFPHF-CA), 187 patients with HFPEF who were undergoing medical therapy (AFPHF-Med), and 196 patients without HFPEF for their first CA (AF-CA). Results After a mean (± SD) follow-up of 36 ± 3 months, 50.8% of patients in the AFPHF-CA group and 52.0% in the AF-CA group remained in sinus rhythm (P = 0.94), compared to only 12.5% in the AFPHF-Med group (P < 0.001). Age (OR: 1.09, 95% CI: 1.02–1.08, P = 0.016), duration of AF history (OR: 1.01, 95% CI: 1.00-1.02, P = 0.017), left atrial diameter (OR: 1.52, 95% CI: 1.06–2.19, P = 0.024), and the type of atrial fibrillation (OR: 4.02, 95% CI: 1.28–12.62, P = 0.017) were consistent multivariable predictors for sinus rhythm maintenance in AFPHF. HF hospitalization was significantly lower in the AFPHF-CA group (0.38 (0,2)) than in the AFPHF-Med group (1.28(0,3), P < 0.001) during the follow-up. Stroke occurred in 18 of 187 (9.63%) patients in the AFPHF-CA group, significantly lower than the AFPHF-Med group, with approximately 31 of 187 (16.58%) (P < 0.01), but not statistically different from AF-CA, where approximately 17 of 196 (8.67%) experienced stroke (P = 0.65). Regarding mortality, death occurred in 12.8% of patients in the AFPHF-Med group, higher than 7.5% in the AFPHF-CA group and 6.6% in the AF-CA group (P = 0.49). Significant improvements in heart function were observed in the AFPHF-CA group compared to the AFPHF-Med group, including reductions in left ventricular end-diastolic diameter (P < 0.001), New York Heart Association classification (P < 0.001), left ventricular mass index (P < 0.001), and left atrial volume index (P < 0.001). HF hospitalization was significantly lower in the AFPHF-CA group compared to AFPHF-Med (P < 0.001). Conclusion CA for AF has showed significant benefits in patients with HFPEF compared to medical treatment alone. These benefits include improvements in heart function, reduced mortality, incidence of stroke, and hospitalizations. Importantly, CA in HFPEF patients showed comparable maintenance of sinus rhythm (SR) and safety outcomes when compared to CA in individuals with normal heart function.